Anti-Ferroptotic Treatment Deteriorates Myocardial Infarction by Inhibiting Angiogenesis and Altering Immune Response - Rebecca A. Stairley; Allison M. Trouten; Shuang Li; Patrick L. Roddy; Kristine Y. DeLeon-Pennell; Kyu-Ho Lee; Henry M. Sucov; Chun Liu; Ge Tao (MDPI AG, 2024)
Mammalian cardiomyocytes have limited regenerative ability. Cardiac disease, such as congenital heart disease and myocardial infarction, causes an initial loss of cardiomyocytes through regulated cell death (RCD). Understanding the mechanisms that govern RCD in the injured myocardium is crucial for developing therapeutics to promote heart regeneration. We previously reported that ferroptosis, a non-apoptotic and iron-dependent form of RCD, is the main contributor to cardiomyocyte death in the injured heart. To investigate the mechanisms underlying the preference for ferroptosis in cardiomyocytes, we examined the effects of anti-ferroptotic reagents in infarcted mouse hearts. The results revealed that the anti-ferroptotic reagent did not improve neonatal heart regeneration, and further compromised the cardiac function of juvenile hearts. On the other hand, ferroptotic cardiomyocytes played a supportive role during wound healing by releasing pro-angiogenic factors. The inhibition of ferroptosis in the regenerating mouse heart altered the immune and angiogenic responses. Our study provides insights into the preference for ferroptosis over other types of RCD in stressed cardiomyocytes, and guidance for designing anti-cell-death therapies for treating heart disease.